Integrating Black Soldier Fly (Hermetia illucens) Larvae Meal in Aquaponics System for Lettuce (Lactuca sativa) Production - Nguka, Samuel Ochieng; Mweresa, Collins Kalwale; Muriithi, Nakhumicha (East African Journal of Agriculture and Biotechnology, 2024)
The adoption of aquaponics systems faces challenges due to the high cost of fish feed, lack of sustainability, and reliance on fishmeal as a primary input. One potential solution to replace fishmeal is the use of black soldier fly larvae (BSFL) in aquaponics. The study aimed to explore the effect of substituting fish meals with BSFL meals on the growth performance of lettuce (Lactuca sativa) in aquaponics. The study employed the Randomized Complete Block Design (RCBD). A total of 135 catfish fingerlings were divided into three groups and stocked in nine water barrels of 100 litres each (filled with 60 litres of water). The fingerlings were fed twice a day for a duration of 56 days after a two-week period of acclimatisation using commercial feed. Water was cycled through the hydroponic media grow bed using an automatic timer, with a 15-minute cycle every hour throughout the day and night. Fish meal was replaced with BSFL meal at three different proportions: 0% (BSFL0), 30% (BSFL30), and 50% (BSFL50). The data collected was analysed using One-Way Analysis of Variance (ANOVA) and Kruskal-Wallis tests, followed by Tukey's ad-hoc and Dunn's tests, respectively, utilising JMP 16 software. The results indicated that the fresh leaf weight was significantly influenced by the diet types (p<0.05). However, no significant effect was observed on root weight, total dry weight, number of leaves, or root length (p>0.05). This study suggests that black soldier fly larvae meal can successfully replace up to 50% of fishmeal in aquaponics without compromising lettuce growth performance. Therefore, promoting the use of black soldier fly larvae meal can contribute to the sustainability of lettuce production in aquaponics.
Keywords: Aquaponics; Hydroponics; Aquaculture; Lettuce; Black Soldier Fly; Fishmeal